Topical Review: The Top Five Peripheral Vision Tools in Sport. Issue 7 (20th July 2021) - Vater, Christian; Strasburger, Hans
Abstract : SIGNIFICANCE: This study summarizes the empirical evidence on the use of peripheral vision for the most-researched peripheral vision tools in sports. : The objective of this review was to explain if and how the tools can be used to investigate peripheral vision usage and how empirical findings with these vision tools might be transferred to sports situations. The data sources used in this study were Scopus, ScienceDirect, and PubMed. We additionally searched the manufacturers' Web pages and used Google Scholar to find full texts that were not available elsewhere. Studies were included if they were published in a peer-reviewed journal, were written in English language, and were conducted in a sports context. From the 10 searched tools, we included the 5 tools with most published studies. In our topical search, we identified 93 studies for the five most-used peripheral vision tools. Surprisingly, none of these studies used eye-tracking methods to control for the use of peripheral vision. Best "passive" control is achieved by tools using (foveal) secondary tasks (Dynavision D2 and Vienna Test System). Best transfer to sports tasks is expected for tools demanding action responses (FitLight, Dynavision D2). Tools are likely to train peripheral monitoring (NeuroTracker), peripheral reaction time (Dynavision D2, Vienna Test System), or peripheral preview (FitLight), whereas one tool did not show any link to peripheral vision processes (Nike SPARQ Vapor Strobe).